Crossing the uncrossable: novel trans‐valley biogeographic patterns revealed in the genetic history of low‐dispersal mygalomorph spiders (Antrodiaetidae, Antrodiaetus) from California. Issue 2 (3rd December 2012) - Hedin, Marshal; Starrett, James; Hayashi, Cheryl
Abstract Antrodiaetus riversi is a dispersal‐limited, habitat‐specialized mygalomorph spider species endemic to mesic woodlands of northern and central California. Here, we build upon prior phylogeographic research using a much larger geographic sample and include additional nuclear genes, providing more detailed biogeographic insights throughout the range of this complex. Of particular interest is the uncovering of unexpected and replicated trans‐valley biogeographic patterns, where in two separate genetic clades western haplotypes in the California south Coast Ranges are phylogenetically closely related to eastern haplotypes from central and northern Sierran foothills. In both instances, these trans‐valley phylogenetic patterns are strongly supported by multiple genes. These western and eastern populations are currently separated by the Central Valley, a well‐recognized modern‐day and historical biogeographic barrier in California. For one clade, the directionality is clearly northeast to southwest, and all available evidence is consistent with a jump dispersal event estimated at 1.2–1.3 Ma. During this time period, paleogeographic data indicate that northern Sierran rivers emptied to the ocean in the south Coast Ranges, rather than at the San Francisco Bay. For the other trans‐valley clade genetic evidence is less conclusive regarding the mechanism and directionality of biogeographic exchange, although the estimated timeframe is similar (approximately 1.8 Ma). Despite the large number of biogeographic studies previously conducted in central California, to the best of our knowledge no prior studies have discussed or revealed a northern Sierran to south Coast Range biogeographic connection. This uniqueness may reflect the low‐dispersal biology of mygalomorph spiders, where 'post‐event' gene exchange rarely erases historical biogeographic signal.